Substantia Nigra Hyperechogenicity: Validation of Transcranial Sonography for Parkinson Disease Diagnosis in a Large Estonian Cohort. (1st January 2016) - Toomsoo, Toomas; Liepelt-Scarfone, Inga; Kerner, Riina; Kadastik-Eerme, Liis; Asser, Toomas; Rubanovits, Inna; Berg, Daniela; Taba, Pille
Abstract : Objectives: Substantia nigra hyperechogenicity is a promising biomarker for Parkinson disease (PD). Substantia nigra hyperechogenicity has previously been established as a useful diagnostic criterion in several European and Asian patient cohorts. However, diagnostic cutoff values for substantia nigra hyperechogenicity remain unknown for most patient populations. This study validated the diagnostic accuracy of substantia nigra hyperechogenicity in a large cohort of patients with PD in Estonia. Methods: The study included 300 patients with PD from Estonia, representing 10% of the national PD patient population, and 200 healthy control participants. To define the optimal cutoff value in the PD cohort, data from a single assessment versus repetitive assessments by transcranial sonography were compared. With the use of 3 repetitive assessments, the diagnostic accuracy of the data was measured. In addition, calculations for percentile values were used to define substantia nigra hyperechogenicity among controls. Results: Our data showed that the multiassessment approach yielded higher diagnostic accuracy than a single assessment ( P = .021). The highest diagnostic accuracy was achieved by using the measurement mean to define substantia nigra hyperechogenicity, which was 0.23 cm 2 (sensitivity, 88.7%; specificity, 92.2%), whereas single measurements detected PD with higher sensitivity (sensitivity, 93.2%; specificity, 85.1%). No significant difference was found between mean and median measurements ( P = .18). Conclusions: This study indicates the diagnostic merit of transcranial sonography in PD diagnosis in an additional population and demonstrates that transcranial sonography of the substantia nigra is a relevant and useful diagnostic tool for patients with PD.